FOOD AS A WAY TO PREVENT DEPRESSIVE CONDITIONS AND DISORDERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In the modern world, eating food has ceased to be a normal physiological need. This article discusses only the features of the influence of certain foods on the psycho-emotional state of students of the Andijan State Medical Institute, in particular foods rich in tryptophan. According to the results of the survey, there is a tendency for the psycho-emotional state to depend on products containing tryptophan, but it does not depend on its percentage in these products. The choice of products depends on the taste preferences of individuals.